2017
DOI: 10.1016/j.tins.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Computations Underlying Detection of Gaps in Sounds and Lateralizing Sound Sources

Abstract: In mammals, acoustic information arises in the cochlea and is transmitted to the ventral cochlear nuclei (VCN). Three groups of VNC neurons extract different features from the firing of auditory nerve fibers, and convey that information along separate pathways through the brainstem. Two of these pathways process temporal information: octopus cells detect coincident firing among auditory nerve fibers, and transmit signals along monaural pathways; and bushy cells sharpen the encoding of fine structure and feed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…The threshold for detecting brief silent gaps in noise provides a valuable analytical tool to measure temporal resolution in auditory processing (Moore, 1997). Gaps as short as 2–3 ms can be detected by humans (Penner, 1977) and rodents (Ison, 1982) and it has been suggested that to detect a 3-ms gap, auditory neurons need to encode onsets and offsets of sounds with a temporal acuity of ∼1 ms (Oertel et al, 2017). Gap-in-noise stimuli have also proven very helpful in determining the ability of the auditory system to encode sound offsets as a parameter independent of sound onsets (Pratt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for detecting brief silent gaps in noise provides a valuable analytical tool to measure temporal resolution in auditory processing (Moore, 1997). Gaps as short as 2–3 ms can be detected by humans (Penner, 1977) and rodents (Ison, 1982) and it has been suggested that to detect a 3-ms gap, auditory neurons need to encode onsets and offsets of sounds with a temporal acuity of ∼1 ms (Oertel et al, 2017). Gap-in-noise stimuli have also proven very helpful in determining the ability of the auditory system to encode sound offsets as a parameter independent of sound onsets (Pratt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system of vertebrates, auditory brainstem neurons are highly specialized to rapidly encode temporal acoustic information (1,2), which is critical for sound localization, escaping danger, and signal extraction from complex acoustic environments (3)(4)(5). These neurons accurately encode acoustic information by generating rapid and temporally precise action potentials (APs) for delivering and refining acoustic cues with a precision in the order of tens of microseconds (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The bushy cells in mammals participate in binaural temporally precise processing pathways and are further subdivided into three distinct subtypes: large spherical (LSBC), small spherical (SSBC), and globular bushy cells (GBC) (2,11). However, the LSBC and SSBC can be distinguished clearly by sizes in cats (12) but not in the other mammals such as guinea pigs and mice (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…Octopus cells are topologically arranged in frequency-ordered laminae and locally wired to bundles of ANFs. The wiring patterns' scheme constitutes their temporal receptive fields (TRFs) (Oertel et al, 2017;Spencer et al, 2018). Octopus cells latency-phase rectify space-time trajectories in their TRFs (Golding and Oertel, 2012;McGinley et al, 2012).…”
Section: Methodsmentioning
confidence: 99%